CEOs' hometown connections and access to trade credit: Evidence from China - Kong, Dongmin; Pan, Yue; Tian, Gary Gang; Zhang, Pengdong (Journal of Corporate Finance, 2020)
In this study, we investigate how informal institutions, namely, chief executive officers' hometown connections with suppliers, impact firms' access to trade credit. Using unique data manually collected from China, we find that hometown connections significantly increase access to trade credit. The hometown effect is more pronounced for non-state-owned firms, firms in provinces with poorly developed financial institutions, and firms whose chief executive officers come from hometowns with a strong merchant guild culture or hold an important position in the hometown's chamber of commerce. We suggest two plausible channels for the hometown effect: information and social trust. Overall, this study contributes to the literature by documenting how hometown connections help firms to obtain external financing in emerging markets.